2003
DOI: 10.1177/154193120304700129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Viewpoint Displacement on Navigational Performance in Virtual Environments

Abstract: Viewpoint tethering, as a way of integrating information from both egocentric and exocentric frames of reference, has been proposed as a means of supporting efficient navigation in virtual environments. In this paper, we report our latest findings on the effects of tether length on navigational performance. Twelve volunteers participated in an experiment in which they were instructed to control an aircraft-shaped cursor flying through a set of virtual tunnels and to answer questions about the environment. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Furthermore, reducing the amount of terrain viewable (small GFOV) produces the same sort of keyholing that, as we saw in the flight path tracking data, disrupts the ability to maintain position and spatial orientation. It seems that the larger GFOV supports a greater, more continuous calibration of the display locations with outside world locations, as more points in the terrain may be available to cognitively link the two views through some form of visual momentum (Woods, 1984), a finding consistent with recent work by Wang and Milgram (2003).…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, reducing the amount of terrain viewable (small GFOV) produces the same sort of keyholing that, as we saw in the flight path tracking data, disrupts the ability to maintain position and spatial orientation. It seems that the larger GFOV supports a greater, more continuous calibration of the display locations with outside world locations, as more points in the terrain may be available to cognitively link the two views through some form of visual momentum (Woods, 1984), a finding consistent with recent work by Wang and Milgram (2003).…”
Section: Discussionsupporting
confidence: 74%
“…As explained earlier, this recommendation does not strictly hold when global performance is paramount. From both a global and a local performance perspective, an important additional consideration is the length of the tether, a topic not dealt with in the present article, but it has been shown elsewhere that longer tethers generally lead to improved global performance (Wang & Milgram, 2003).…”
Section: Conclusion and Discussionmentioning
confidence: 97%
“…Although each of these parameters can affect the tether's behavior, we focus here on the tether spring constant and damping coefficient as critical parameters, an understanding of whose impact will shed light on some of the unique strengths potentially introduced by dynamic tethering. (A study of the effect of a third critical parameter, tether length, has been reported elsewhere, in Wang & Milgram, 2003. ) equivalent Spring Constant…”
Section: Dynamic Viewpoint Tetheringmentioning
confidence: 99%
“…It is not surprising therefore that no significant performance differences were observed in global awareness performance. Our follow-up research to the study reported here (Wang & Milgram, 2003) is thus investigating how these other characteristics affect global navigation performance.…”
Section: Tunnel Shape Recognition As a Secondary Taskmentioning
confidence: 89%